Spatiotemporal evolution of the thermal environment and influencing factors in Kashgar City’s Urban Expansion - Jiaxing Yan; Wenli Wu; Chunlan Du; Xutong Zhang; Xinyan Sheng (PLoS ONE, 2026)
Under the dual pressures of global warming and rapid urbanization, the mechanisms governing the evolution of high-temperature environments in arid-zone cities demand systematic analysis. This study investigates the spatiotemporal evolution characteristics and multidimensional influencing factors of urban expansion and thermal environments in the Kashgar region. As a representative city in China’s arid western region, the analysis utilizes multi-source remote sensing data and socioeconomic statistics from 2010 to 2024. Methods including urban expansion indices, surface temperature inversion, and geographic detector models were employed to reveal spatiotemporal patterns linking urban form changes and thermal environments. The findings indicate: (1) Kashgar’s urban expansion exhibits significant spatial heterogeneity, with construction land expansion characterized by stable central areas and rapid peripheral growth. Marginal expansion dominates the thermal environment, where the township-Mulatibag urban-rural fringe has emerged as a new growth pole for thermal expansion. (2) Kashgar’s thermal environment continues to deteriorate, with the area affected by high temperatures increasing by an average of 19.55% annually. The spatial pattern has undergone a three-stage evolution: punctual breakthroughs, cluster aggregation, and contiguous spread. The low-temperature ecological corridor system has systematically shrunk, and the city’s thermal environment regulation capacity shows a significant downward trend. (3) A strong positive correlation exists between Kashgar’s urban expansion and its thermal environment. This correlation exhibited a trend of “initial strengthening followed by weakening” over the fifteen-year period. (4) Factors influencing high temperatures exhibit multidimensional interactions. Among anthropogenic factors, impervious surfaces and population density jointly intensify high-temperature severity through a dual-factor amplification effect. Conversely, natural factors such as vegetation and water bodies exert a negative mitigating influence.